Flow regimes during surfactant flooding: The influence of phase behaviour. (15th January 2019) - Alzahid, Yara A.; Mostaghimi, Peyman; Walsh, Stuart D.C.; Armstrong, Ryan T.
Highlights: Surfactant–oil–brine phase behaviours of different Winsor types were identified. Displacement processes were characterised for the three Winsor types. Capillary and viscosity numbers are the main parameters considered. Winsor type III achieved the highest recovery at the lowest capillary number. Interfacial tension, local equilibrium and viscosity are key to achieving high recovery. Abstract: Surfactant flooding is one of the most widely adopted enhanced oil recovery strategies whereby microemulsion is formed in situ during immiscible displacement. It is expected that local equilibrium is achieved during surfactant flooding and that resulting microemulsion phase properties directly influence the flow physics and thus, oil recovery. We consider phase behaviour of a surfactant–oil–water system that can form either Winsor type II−, III or II+ microemulsion. Water, polymer and Winsor type surfactant solutions are injected into oil saturated polydimethylsiloxane microfluidic chips and imaged under continuous flow at various Capillary numbers and Viscosity ratios. Images are analysed for displacement patterns and oil recovery. Flow regimes are explained by considering the equilibrium interfacial tension (IFT) and viscosity of the formed microemulsion phase. Displacement of oil by injected fluids was dominated by capillary fingering at low flow rates. At higher flow rates, type III microemulsion develops viscous fingering while type II− develops stable displacement due to the microemulsion phases being of high and low viscosity, respectively. This report highlights that the difference between stable/unstable displacement during surfactant flooding is influenced by surfactant–oil–water phase behaviour.